Metabolomics Profiles Associated with the Treatment of Zuojin Pill on Patients with Chronic Nonatrophic Gastritis - Ma, Xiao; Xie, Shuying; Wang, Ruilin; Wang, Zhongxia; Jing, Manyi; Li, Haotian; Wei, Shizhang; Liu, Honghong; Li, Jianyu; He, Qingyong; Zhao, Yanling (Frontiers in Pharmacology, 2022)
Objective: Chronic non-atrophic gastritis (CNG) is the most common seen digestive diseases. In China, Zuojin pill (ZJP) is thought as the effective formulae for CNG. However, its efficacy and mechanism has never been explored. In order to understand how and why ZJP demonstrated therapeutic effect on CNG, a clinical trial was conducted. The metabolomics was used to explore its deep mechanism. Methods: A total of 14 patients with CNG were recruited from October 2020 to March 2021 (ChiCTR2000040549). The endoscopy and histopathological changes were evaluated as efficacy. Serum samples were prepared and detected by performing widely targeted metabolome using UPLC. Multivariate statistical analysis was conducted to distinguish the potential differential metabolites and signaling pathways. Finally, the signal related inflammatory factors containing COX-2, IL-4 and IL-17 were confirmed via immunohistochemical staining and enzyme-linked immuno sorbent assay. Results: ZJP was able to alleviate the several index of mucosal injury under endoscopy and histology. erosion and bile reflux but not red plaques, hemorrhage were down-regulated by ZJP. In addition, it could remarkably alleviate the active chronic inflammation. Fourteen potential metabolites containing Hypoxanthine, Adipic Acid, D-Ribono-1,4-lactone, L-Sepiapterin, Imidazoleacetic acid, Sebacate, ADP-ribose, 4-Hydroxybenzyl alcohol, 11,12-EET, 15-OxoETE, 12-OxoETE, (±)8-HETE, Glycyrrhizinate and DL-Aminopimelic acid were discriminated by Metabolomics. Moreover, certain amino acid metabolism got significance during the disease progress and treatment. The related inflammatory factors including COX-2, IL-4 and IL-17 were inhibited by ZJP in both mucosa and serum. Conclusion: All these result indicated that ZJP partially plays as inflammatory suppressor to regulate comprehensive metabolism disorders. This might be the important mechanism for ZJP to treat CNG.